Restoration of pretreated palm oil mill effluent using TiO2 based photocatalytic system: An optimization study. Issue 4 (January 2020) - Nawaz, R; Chong, F K; Ho, Y C; Isa, M H; Lim, W H
Abstract: Phenolic compounds found in pretreated palm oil mill effluent (pre-POME) pose severe threat to aquatic ecosystem and human health due to their build-up in the environment and high toxicity. Thus, the removal of phenolic compounds from pre-POME is necessary to preserve environmental quality and protect human health. In this paper, the optimized degradation of phenolic compound, gallic acid (GA) from pre-POME under visible light assisted TiO2 based photocatalysis is reported. TiO2 nanoparticles (NPs) were synthesized by chemical precipitation technique followed by characterization with X-ray diffraction (XRD), diffuse reflectance UV-Vis spectroscopy (DR-UV-Vis) and field emission scanning electron microscopy (FESEM). The effect of process variables such as loading of TiO2 and H2 O2 dose on the degradation of GA from pre-POME was investigated and optimized using response surface methodology (RSM) based on central composite design (CCD). Spherical shaped anatase phase TiO2 NPs with size 45.47 nm and band gap (Eg) of 3.16 eV were obtained. The results demonstrated that both variables, TiO2 loading and H2 O2 dosage showed positive effect on GA degradation. The highest removal of GA from pre-POME (71.20%), from 44.85 ppm of initial concentration was observed for the optimal TiO2 loading of 0.88 g/L, H2 O2 dosage of 8.5 wt% and 2 h reaction under visible light irradiation. The use of H2 O2 combined with TiO2 NPs indicated a great potential for the removal of GA, which has been pointed out as the major phenolic compounds in pre-POME.